Role of spontaneous cycle follicular monitoring in unexplained infertility: an observational study - Vandana Mohan; Kanika Chopra; Manju Puri; Pikee Saxena (New Indian Journal of OBGYN, 2022)
Objective: The incidence of unexplained infertility is high and thus there is a need to assess usefulness of unexplored modalities i.e. ultrasonographic follicular monitoring and endometrial changes and its correlation with hormonal levels in spontaneous menstrual cycle. Our study aimed to detect subtle defects responsible for the same. Methodology: It was an observational study conducted in the infertility clinic of Lady Hardinge Medical College, New Delhi, India. Fifty women with unexplained infertility were included in the study. The subjects were called on day 2-3 of onset of menses for a baseline transvaginal ultrasound for antral follicular count, endometrial thickness and hormonal profile. Follow-up ultrasonographic monitoring was done till ovulation was documented. Hormonal profile was done on day of dominant follicle of 18-20 mm and on day 21, serum progesterone levels were done. Results: The mean age of study group was 26.48±3.3 years. Primary infertility was seen in 66% cases and secondary infertility in 34%. Seventy eight percent women had at least one or a combination of subtle defects in their monitored cycles. The mean antral follicle count was 13.8±5.17. Only one woman had antral follicle count of less than 5. 30% of women had levels of FSH more than 10 IU/L and levels of serum estradiol more than 80 pg/ml. Luteal phase defect and premature LH surge was seen in 34 % women each. Conclusion: Spontaneous cycle follicular monitoring is a useful tool to provide insight into the subtle defects like premature depletion of ovarian reserve, defective folliculogenesis, poor oocyte quality, premature luteinization, luteinized unruptured follicular syndrome contributing to unexplained infertility. Transvaginal sonographic assessment of a spontaneous cycle thus, appeared to be a useful addition in the investigative work-up of women with unexplained infertility.